HCI International 2018 -- posters' extended abstracts. 20th International Conference, HCI International 2018, Las Vegas, NV, USA, July 15-20, 2018, Proceedings /: 20th International Conference, HCI International 2018, Las Vegas, NV, USA, July 15-20, 2018, Proceedings. Part II : (2018) - Unknown
No abstract available